PENERAPAN FISIOTERAPI DADA TERHADAP BERSIHAN JALAN NAPAS TIDAK EFEKTIF PADA ANAK DENGAN PNEUMONIA - Bunga Karina Zulfa; Armenia Diahsari; Dwi Prasetyorini (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Pneumonia is an acute infection of the lung parenchyma characterized by inflammation of the alveoli due to bacterial, viral, or fungal infection. This condition often leads to increased secretion production, resulting in ineffective airway clearance problems in children. This study aims to determine the effectiveness of the application of chest physiotherapy combined with suctioning on ineffective airway clearance problems in children with pneumonia in the East Aster Ward of Dr. Sardjito General Hospital. This study used a qualitative descriptive method with a case study approach. The research subject was a 1-year-old child with a medical diagnosis of pneumonia. Data were collected through interviews with the patient's parents, observation, physical examination, and medical record documentation studies. The interventions provided were chest physiotherapy, percussion, and vibration for three consecutive days, as well as suctioning on the third day. The assessment results showed that the patient experienced ineffective airway clearance, characterized by secretion accumulation in the nose and throat accompanied by coughing. After chest physiotherapy for three days and suctioning on the third day, there was a decrease in secretion accumulation, improved airway patency, and better airway clearance. The patient appeared more comfortable and secretions became easier to expel. The application of chest physiotherapy combined with suctioning is effective in facilitating secretion mobilization and expulsion, thereby improving ineffective airway clearance problems in children with pneumonia. This intervention can be used as a nursing measure to support the management of pneumonia patients with airway clearance impairment.